Analysis of PD‐L1 expression and T cell infiltration in different molecular subgroups of diffuse midline gliomas. Issue 6 (17th October 2019) - Jha, Prerana; Manjunath, Niveditha; Singh, Jyotsna; Mani, Kalaivani; Garg, Ajay; Kaur, Kavneet; Sharma, Mehar C.; Raheja, Amol; Suri, Ashish; Sarkar, Chitra; Suri, Vaishali
Abstract : Diffuse midline gliomas (DMGs) are rare and devastating tumors with limited therapeutic options. Programmed death‐ligand 1 (PD‐L1) expression represents a potential predictive biomarker for immunotherapy. One hundred and twenty‐six DMGs (89 adult and 37 pediatric) were assessed for immune profile (PD‐L1, cluster of differentiation (CD3, CD8) and genetic markers (mutation in 27th amino acid of histone H3 (H3K27M), alpha thalassemia/mental retardation syndrome X‐linked (ATRX), isocitrate dehydrogenase 1 (IDH1), p53) by immunohistochemistry. Sanger sequencing was done for IDH1 and H3K27M. The thalamus was the commonest site. Four molecular subgroups of DMGs were identified. H3K27M mutation was more frequent in children ( P = 0.0001). The difference in median overall survival (OS) was not significant in any of the four molecular subgroups ( P > 0.05). PD‐L1 expression was significantly higher in H3K27M/IDH1 double‐negative adult glioblastomas (GBMs) ( P = 0.002). Strong PD‐L1 expression was more frequent in grade IV tumors and thalamic location, although the difference was not significant ( P = 0.14 and P = 0.19 respectively). Positive PD‐L1 expression was significantly associated with high tumor‐infiltrating lymphocytes count ( P  < 0.05). There was no significant difference in median OS in PD‐L1‐positive versus negative cases among four genetic subgroups ( P > 0.05). On univariate analysis, there was no direct correlation of PD‐L1 with any genetic alteration, except H3K27M mutation ( P = 0.01). CD3 infiltration was similar in both adults and pediatric ages (84.3% and 78.4%, respectively) while CD8 expression was significantly greater in adults compared to children (74.1% vs 37.8%, P = 0.0001). This is the first comprehensive analysis highlighting molecular and immune profiles of DMGs. Despite molecular and clinicopathological diversity, overall survival in DMGs remains dismal. Multicentric studies with larger numbers of cases should be undertaken for stratifying DMGs according to their age, immune and molecular profiles, to develop effective immunotherapies.